Clinical application of a modified pancreatojejunostomy technique for laparoscopic pancreaticoduodenectomy. Issue 10 (October 2019) - Du, Yusheng; Wang, Ji; Li, Ying; Ma, Hongqin; Liu, Li; Zhu, Yuxiao; Zhao, Wenxing
Abstract: Background: The aim of this study was to present a modified pancreatojejunostomy technique for laparoscopic pancreaticoduodenectomy (LPD) and to evaluate its safety and reliability. Methods: Clinical data from 67 patients who underwent LPD at a single center, from September 2016 to December 2017 were retrospectively collected and analysed. Of these patients, 31 cases were subjected to modified pancreatojejunostomy (modified group), and 36 cases received duct-to-mucosa pancreatojejunostomy (control group) for LPD. We compared and analysed the operative outcomes and postoperative complications between the patients in the two groups. Results: All LPDs were successfully completed. The mean operation time for pancreatojejunostomy in the modified group was obviously lower than that of the control group (30.9 ± 6.6 min vs 45.3 ± 6.1 min, P < 0.01), and the total operative time was also shorter (321.8 ± 63.6 min vs 362.2 ± 59.6 min, P < 0.05) in the modified group. The overall incidence of postoperative complications was similar (29.0% vs 30.6% P = 0.724). Clinically relevant grade B/C POPF occurred in 2 patients (6.5%) in the modified group and 3 patients (8.3%) in the control group (P = 0.947); All cases were cured using conservative treatment. Conclusions: Our modified pancreatojejunostomy technique is safe, effective and easy to manipulate and learn following LPD.